Time Cost Trade Off (TCTO) Analysis by Considering Overtime Working Hours, and Labor Factors on the Outer East Ring Road (OERR) Surabaya Project (STA 0+000 – STA 5+875) - Isnaini, Nurul; Prajitno, Achmad Faiz Hadi (Jurnal Transportasi: Sistem, Material, dan Infrastruktur, 2023)
In the implementation of construction projects, unwanted things often occur, including delays. Several factors cause these delays: inadequate material stock, delays in material arrival, damage to some tools, and human resources. Thus, it can affect the cost budget incurred to be bloated or excessive compared to the planned cost budget. In this study, an acceleration analysis was carried out on the Outer East Ring Road (OERR) Surabaya project using the Time Cost Trade Off (TCTO) method. Based on field conditions, the alternative to be used was to increase overtime working hours and increase the number of laborers. After the acceleration analysis, it was obtained that the acceleration alternative with the additional working hours (overtime) obtained an acceleration time of 224 days, with a total cost of IDR 95.435.963.465 from the normal cost of IDR 92.207.904.586. It was obtained that the acceleration alternative using additional working hours (overtime) generated a time efficiency of 17.04%, while cost efficiency decreased by 0.01%. While for the alternative of additional labor, the acceleration time was 130 days, with a total cost of IDR 95.438.444.127 from the normal cost of IDR 92.207.904.586. It was obtained that the acceleration alternative using additional working hours (overtime) generated a time efficiency of 51.85%, while cost efficiency decreased by 0.02%.